PERFORMANS INDUK DAN PERTUMBUHAN PRASAPIH SAPI PERANAKAN ONGOLE DAN SAPI SILANGAN SIMMENTAL â PERANAKAN ONGOLE DI KELOMPOK VILLAGE BREEDING CENTER DAN NON VILLAGE BREEDING CENTER DI DAERAH ISTIMEWA YOGYAKARTA - , FEBRI ARIYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research aims to determine cow performance of Ongole Grade (OG) and Simmental Ongole Crossbred Cattle (SOCC) in terms of feed consumption, body condition score (BCS), post partum estrus (PPE) and preweaning growth calf at village breeding center (VBC) compared non village breeding center (NVBC) OG. This research was done on April until December 2012 in 6 groups VBC (Sumber Ayu, Andhini Rahayu, Ngudi Makmur I, Andhini Mulyo, Trimanunggal Lembusuro, Trihandini Rejo) vs 2 groups NVBC (Sedyo Makmur, Andhini). The material used are OG and SOCC at VBC were 22 heads